Symmetry in Applied Continuous Mechanics - Baleanu, Dumitru; Marin, Marin; Vlase, Sorin (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Engineering practice requires the use of structures containing identical components or parts, useful from several points of view: less information is needed to describe the system, design is made quicker and easier, components are made faster than a complex assembly, and finally the time to achieve the structure and the cost of manufacturing decreases. Additionally, the subsequent maintenance of the system becomes easier and cheaper. This Special Issue is dedicated to this kind of mechanical structure, describing the properties and methods of analysis of these structures. Discrete or continuous structures in static and dynamic cases are considered. Theoretical models, mathematical methods, and numerical analyses of the systems, such as the finite element method and experimental methods, are expected to be used in the research. Machine building, automotive, aerospace, and civil engineering are the main areas in which such applications appear, but they are found in most engineering fields.